Environmental fatigue crack propagation behavior of β-annealed Ti-6Al-4V alloy in NaCl solution under controlled potentials. (June 2018) - Ahn, Soojin; Jeong, Daeho; Kwon, Yongnam; Goto, Masahiro; Sung, Hyokyung; Kim, Sangshik
Highlights: FCP behavior of β-annealed Ti6Al4V were examined in NaCl under different potentials. Cleavage characteristics of β-annealed Ti6Al4V changed in NaCl solution. Characteristics of crack bifurcation of β-annealed Ti6Al4V changed with different environment and R ratio. Abstract: The fatigue crack propagation (FCP) behavior of β-annealed Ti-6Al-4V (Ti64) alloy was examined in air and 0.6 M NaCl solution under anodic and cathodic applied potentials and at two different R ratios of 0.1 and 0.7. β-annealed Ti64 alloy was sensitive to environmental FCP in NaCl solution under both anodic and cathodic applied potentials at an R ratio of 0.1, while the environmental effect was almost negligible at an R ratio of 0.7. The extent of crack branching in air and at an R ratio of 0.1 decreased substantially in NaCl solution and/or at an R ratio of 0.7. The EBSD (electron backscatter diffraction) and SEM (scanning electron microscope) fractographic analyses on the FCP tested specimens showed that microstructure-sensitive cracking, rather than crystallographic cleavage cracking, became encouraged in NaCl solution and/or high R ratio. It was suggested that the extent of crack branching played an important role in determining the environmental FCP behavior of β-annealed Ti64 alloy.